Digital Image Steganography Utilizing Database Identification - Alobaydi, Esraa Khalid Ahmed; Aldewachy, Omar Muayad Abdullah; Alkhayat, Rayan Yousif Yacob (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This paper aims to apply digital image steganography based on a database through some proposed steps, first is converting the stego image(colored image) and covered (original) image into there 24-bit binary representation form, and the second step is segmenting the derived representation from the previous step into regions (sub-images) with size 10 (10*10), the third step is constructing a number of databases, each consists of 100 records and each record contains 24-bit pixel representation, next step is applying shifting process starting from the least significant bit LSB, the number of shifting times is depending on a proposed equation for each record, we repeat this process for each region's database in order to get a more secured information, next step is hiding (embedding) these databases into the covered image depending on a proposed method, finally, we apply a proposed method in order to eliminate any distortion derived after embedding the stego image into the original one after applying the proposed steganography method.